A rapid-responsive fluorescent probe based on coumarin for selective sensing of sulfite in aqueous solution and its bioimaging by turn-on fluorescence signal. (December 2017) - Wang, Lei; Li, Wenxuan; Zhi, Wenjing; Ye, Dandan; Wang, Yun; Ni, Liang; Bao, Xu
Abstract: A solo turn-on fluorescent probe based on the coumarin and selective deprotection of the levulinate group has been developed for detection of sulfite with rapid response time (only a few seconds). The probe1 exhibited sufficiently satisfactory selective response to sulfite among various interferential anions, and high sensitivity with the detection limit as low as 85 nM. Upon interaction with sulfite, the probe1 rendered turn-on response by exhibiting prominently bluish-green fluorescence under physiological condition. The mechanism of the interaction has been well confirmed by the changes in ultraviolet visible (UV-vis) absorption spectra and electrospray ionization (ESI) mass spectra. Importantly, probe1 has been successfully applied to detect sulfite in its vitro studies with cancer cells. Graphical abstract: Highlights: The probe is capable of detecting SO3 2- within 30 s. The probe exhibits high sensitivity with the detection limit as low as 85 nM. The probe displays sufficiently satisfactory selective response to sulfite ions among various interferential anions. The probe can be successfully applied to detect sulfite in its vitro studies with cancer cells.